2017
DOI: 10.21815/jde.017.022
|View full text |Cite
|
Sign up to set email alerts
|

Dental Education Required for the Changing Health Care Environment

Abstract: To be able to meet the demands for care in 2040, dental graduates will need to address challenges resulting from the rapidly changing health care environment with knowledge and sets of skills to build on current standards and adapt to the future. The purposes of this article are to 1) analyze key challenges likely to evolve considerably between now and 2040 that will impact dental education and practice and 2) propose several sets of skills and educational outcomes necessary to address these challenges. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 33 publications
0
54
0
5
Order By: Relevance
“…8 Those researchers suggested that the CRA was a useful tool for risk stratiication, which is similar to our indings in which patients experienced a signiicantly higher percentage of new caries-related treatments based on increasing categories of risk. [17][18][19] Conclusion This study found that the dental school's CRA tool when used by students was able to identify patients at increased risk of needing treatment associated with caries over time; however, the evidence suggests that, for prediction purposes, the tool is best at helping draw a distinction between regular risk (low/moderate) and increased risk (high risk). After the caries risk is assigned, the following tab in our caries risk assessment form is the caries management plan, where students document the proposed plan agreed upon with the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Those researchers suggested that the CRA was a useful tool for risk stratiication, which is similar to our indings in which patients experienced a signiicantly higher percentage of new caries-related treatments based on increasing categories of risk. [17][18][19] Conclusion This study found that the dental school's CRA tool when used by students was able to identify patients at increased risk of needing treatment associated with caries over time; however, the evidence suggests that, for prediction purposes, the tool is best at helping draw a distinction between regular risk (low/moderate) and increased risk (high risk). After the caries risk is assigned, the following tab in our caries risk assessment form is the caries management plan, where students document the proposed plan agreed upon with the patient.…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of the thought process behind assigning risk based on the factors present would be interesting and could lead to better understanding of a patient's placement into a speciic risk category and assist in the assessment of students' critical thinking skills. [17][18][19]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have made clear the importance of incorporating oral health in global health efforts and the need to address global oral health inequities 1,5,32,33 . Equipping the future oral health workforce with the knowledge and tools required to address oral health inequities is critical for global health efforts 11,34,35 . Dental schools have responded by integrating global health competencies into their curricula, including HSDM with the launch of its Global Oral Health Initiative in 2011 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Tema que surgió como consecuencia del proceso de construcción del currículo de Cariología en EE.UU. (8) .…”
Section: Discussionunclassified
“…La interpretación de la etiopatogenia de la enfermedad ha sufrido cambios fundamentales en los últimos años, pasando de la visión de una enfermedad infecciosa y transmisible causada por una sola especie bacteriana, a una visión de enfermedad ecológica no transmisible causada por el desequilibrio del biofilm dental como consecuencia del consumo frecuente de azúcares (5)(6)(7) . Adicionalmente, la formación del odontólogo requiere de la incorporación de herramientas para comprender el rol de factores socioculturales en el desarrollo de la enfermedad y la importancia que durante el manejo integral de los pacientes se incorporen todos estos conceptos (8) . En este contexto, la formación del nuevo odontólogo exige una cuidadosa revisión de las competencias profesionales declaradas en su plan de estudios.…”
Section: Introductionunclassified